Foreign Exchange Reaction on the Announcement of Political News: Evidence of Indonesia during Presidency Changes - Theodorus, Jose Felix (2010)
Exchange rate is very important topic to look at because it affects many people from government to private investor to people at large. They interested in exchange rate because it affects investment strategy, government policy,spending, etc. This dissertation looks at the relationship between exchange rate and both political factors and economic indicator especially interest and inflation rate. This dissertation used Riley and Luksetich (1990) method to find exchange rate reaction during changes in presidency. There are 3 main findings which this dissertation found important to understand the relationship between exchane rate and both political factors and economic indicators. One,foreign exchange rate market is efficient in semi strong form. Two, political news is very useful elements to be considered and used to forecast exchange rate movement in the short term. Three, inflation and interest rate are very poor indicators to predict exchange rate movement in the short run.